2015
DOI: 10.1016/bs.pmbts.2015.06.014
|View full text |Cite
|
Sign up to set email alerts
|

RPE and Choroid Mechanisms Underlying Ocular Growth and Myopia

Abstract: Myopia is the most common type of refractive errors and one of the world’s leading causes of blindness. Visual manipulations in animal models have provided convincing evidence for the role of environmental factors in myopia development. These models along with in vitro studies have provided important insights into underlying mechanisms. The key locations of the retinal pigment epithelium (RPE) and choroid make them plausible conduits for relaying growth regulatory signals originating in the retina to the scler… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
82
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 91 publications
(84 citation statements)
references
References 99 publications
2
82
0
Order By: Relevance
“…The increased eye size is restricted to the posterior, retinal portion, leaving the anterior segment essentially unchanged. The posterior portion is enclosed by the RPE, and numerous studies point to the interaction between RPE and the surrounding sclera to be necessary for control of eye growth [44][45][46][47]. However the mechanism by which the eye becomes enlarged is not simply loss of RPE function.…”
Section: Discussionmentioning
confidence: 99%
“…The increased eye size is restricted to the posterior, retinal portion, leaving the anterior segment essentially unchanged. The posterior portion is enclosed by the RPE, and numerous studies point to the interaction between RPE and the surrounding sclera to be necessary for control of eye growth [44][45][46][47]. However the mechanism by which the eye becomes enlarged is not simply loss of RPE function.…”
Section: Discussionmentioning
confidence: 99%
“…RDH5 is best known for its role in the regeneration of 11-cis retinal in the visual cycle, but the enzyme has also been reported to be capable of producing retinoids suitable for retinoic acid signaling 76,77 . Evidence from animal models implicates retinoic acid in eye growth regulation 12 , and retinal all-trans retinoic acid levels are elevated in a guinea pig model of myopia 78 . Thus the same haplotype, which has risen to substantial frequencies in some populations (0.38 minor haplotype frequency in South Asians and 0.19 in Europeans https://www.ncbi.nlm.nih.gov/projects/SNP/), may dampen retinoic acid signaling during eye development and growth, and later contribute to chronic photoreceptor dysfunction in older adults.…”
Section: Discussionmentioning
confidence: 98%
“…Phase 2: In diabetic patients with longer duration of disease, the long‐term metabolic abnormalities caused sustained damage of the choroidal vascular cells, occlusion, distortion and local microaneurysm of the choroid capillary, drusen‐like precipitation of the Bruch membrane, atrophy of the choroid, emergence of neovascularization and, finally, DC (Zhu & Wallman ; Kim et al. ; Zhang & Wildsoet ).…”
Section: Discussionmentioning
confidence: 99%
“…Study has shown that at this stage, there was vascular distortion and formation of sinus-like structure between the choroid lobules, which further aggravated the hypoxia and oedema of the choroid, resulting in the increase of CT (Tavares et al 2017). Phase 2: In diabetic patients with longer duration of disease, the long-term metabolic abnormalities caused sustained damage of the choroidal vascular cells, occlusion, distortion and local microaneurysm of the choroid capillary, drusen-like precipitation of the Bruch membrane, atrophy of the choroid, emergence of neovascularization and, finally, DC (Zhu & Wallman 2009;Kim et al 2013;Zhang & Wildsoet 2015).…”
Section: The Role Duration May Plays In the Posterior Pole Choroid Thmentioning
confidence: 99%